Gold wire bond study for automotive application. (November 2020) - Papadopoulos, C.; Villiger, T.; Steiner, S.; Prinz, J.; Morabito, C.; Cammarata, M.; Rodriguez, A.; Kwon, J.; Geilenkeuser, R.; Breuer, D.; Kuechenmeister, F.; Dienelt, J.; et al.
Abstract: In this publication, the influence of bond wire material properties (Au 2N/4N), and plasma pre-treatment on the wire-bond strength is investigated based on Automotive Electronics Council Qualification (AEC-Q100) and customer requirements. The wire pull force capability is compared, and growth of the Au/Al intermetallic phase (IMP) is analyzed with scanning electron microscope (SEM) cross sections after High Temperature Storage Life (HTSL, 150 °C), Temperature Cycling (TC, −65 °C – 150 °C) and unbiased Humidity Accelerated Stress Test (uHAST, 130 °C/85% relative humidity (RH)). The effect of plasma treatment prior bonding on 2N and 4N wires is discussed and compared to the results without plasma treatment prior wire bonding. Furthermore, test acceleration by using elevated test temperatures (HTSL, 250 °C) is shown and the wire capability compared.